Compositional Alteration of Fin Fish due to Climate Change Induced Oscillation of Hydrological Parameters - Abhijit Mitra (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2015)
Climate change in the lower Gangetic delta has caused an increase in water temperature and altered the salinity and pH of the aquatic phase. Such changes have caused a significant alteration in the diversity spectrum of fin fishes prevailing in the system. The Shannon Weiner species diversity indices computed from the catch of commercially important fin fishes and trash fin fishes (sample size = mean of 20 catches of 100 kg each from each landing station; duration 1984 - 2014) indicate a pronounced temporal variation both in the western and central sector of Indian Sundarbans that have contrasting geo-physico-chemical features. The aquatic phase of the western Indian Sundarbans exhibited a gradual rise of commercially important fin fish diversity, while in the central sector the diversity of the trash fish variety increased over a period of more than two decades. The trash fin fish variety here indicates low priced fishes that are mostly used for poultry and fish feed preparation after sun drying.